Respuesta :
[tex]{ \qquad\qquad\huge\underline{{\sf Answer}}} [/tex]
Here we go ~
[tex]\qquad \sf \dashrightarrow \: f(x)= {6}^{x} [/tex]
we need to find f'(2) = ??
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (x) = \displaystyle \sf \lim_{h \to0} \: \: \dfrac{f(x + h) - f(x)}{h} [/tex]
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (x) = \displaystyle \sf \lim_{h \to0} \: \: \dfrac{6 {}^{x + h} - 6 {}^{x} }{h} [/tex]
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (x) = \displaystyle \sf \lim_{h \to0} \: \: \dfrac{6 {}^{x + h} - 6 {}^{x} }{h} [/tex]
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (x) = \displaystyle \sf \lim_{h \to0} \: \: \dfrac{6 {}^{x }( 6 {}^{h} - 1)}{h} [/tex]
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (x) =\: 6 {}^{x} \: log_{e}(6) [/tex]
Now, plug in 2 for x ~
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (2) =\: 6 {}^{2} \sdot log_{e}(6) [/tex]
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (2) =\: 36 \sdot (1.79)[/tex]
[tex]\qquad \sf \dashrightarrow \: f {}^{ \prime} (2) =64.44[/tex]